On a class of fuzzy sets defined by Orlicz functions - Et, Mikail; Mursaleen, Mohammad; Isik, Mahmut (Univ Nis, Fac Sci Math, 2013)
The idea of difference sequences of real (or complex) numbers was generalized by Et and Colak [9]. In this paper, using the difference operator Delta(m) and an Orlicz function, we introduce and examine a class of sequences of fuzzy numbers. We study some of their properties like completeness, solidity, symmetricity etc. We also give some inclusion relations related to this class.
Keywords: Orlicz function; fuzzy number; difference sequence